Retroviruses: Reversing the dogma of life - A review - Shobha Potlakayala; Andrew Miles; Shrina Patel; Aayushi Patel; Gregory Wolbrette; Shriya Kane; Nicole Lookfong; Abigayle Noble; Xiuli Shen; Sairam Rudrabhatla (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2022)
Retroviruses replicate by means of reverse transcription, utilizing an enzyme, reverse transcriptase, in conjunction with integrase. Their elements have been found in humans, animals, fungi, plants, and bacteria alike. For millions of years, these elements are continuing to integrate into the eukaryotic genomes and affecting these organisms to date. Specifically, endogenous retroviruses have been shown to comprise a large portion of vertebrate genomes. Studies have shown that these microscopic viral elements within the genome are influencing gene expression and in turn evolution, by affecting adjacent gene expression patterns. In the medical field, these retroviruses can present illnesses for many, such as those living with Human Immunodeficiency Virus or Human T Cell Lymphotropic Viruses. With modern advances in bioinformatics, genomics, and drug design, retroviruses are being understood much better. A multitude of new discoveries is advancing the scientific communities to mitigate, prevent, and hopefully cure serious medical ailments caused by retroviruses.